# Prove that $\gcd{(a^b-1,a^c-1)}=a^{\gcd{(b, c)}}-1$

The question is as follows:

Let $a, b, c$ be three positive integers. Prove that $\gcd{(a^b-1,a^c-1)}=a^{\gcd{(b, c)}}-1$.

This is a homework assignment. I've tried using Bezout's theorem. But, to no avail. Also, it's easy to show that the R.H.S. divides the L.H.S., but I can't show the converse. Hints are welcome.

To avoid any discussion about the meaning of $\gcd (0,0),$ assume $a>1.$ Let $b=b'x$ and $c=c'x$ where $x=\gcd (b,c).$ So $b'$ and $c'$ are co-prime positive integers. Let $d=a^x.$ Now $d-1$ divides both $d^{b'}-1$ and $d^{c'}-1,$ so $$\bullet \quad \gcd (a^b-1,a^c-1)=\gcd (d^{b'}-1, d^{c'}-1)\geq d-1=a^x-1=a^{\gcd (b,c)}-1.$$ On the other hand, since $\gcd (b',c')=1$, take integers $x, y$ with $b'x+c'y=1.$ For brevity let $z=\gcd (d^{b'}-1,d^{c'}-1).$ We have $$d^{b'}\equiv d^{c'}\equiv 1 \pmod z.$$ Therefore $$d-1\equiv d^{b'x+c'y}-1\equiv (d^{b'})^x(d^{c'})^y-1\equiv 1^x1^y-1\equiv 0\pmod z.$$ That is, $z|(d-1).$ So $z\leq d-1,$ and $$\bullet \quad \gcd (a^b-1,a^c-1)=z\leq d-1=a^{\gcd (b,c)}-1.$$

• Like this solution – S. Y Sep 21 '16 at 5:04

Show the L.H.S. is a factor of $a^{b-c}-1$, then take another look at Euclid's Algorithm.